The components of spirituality in the business organizational context : the case of Malaysia - Mohammed Kamil, Naail; Al-Kahtani, Ali Hussain; Sulaiman, Mohamed (Society for Business Research, 2011)

(untitled)
Although the phenomenon of spirituality in the workplace has received enormous attention from other religious faiths, the construct of Islamic spirituality has not been much explored. This empirical study attempts to enrich the understanding of the spirituality in the workplace phenomenon from Islamic management perspective. The survey data used for this empirical research was drawn from 405 Muslim employees in business organizations in Malaysia. After yielding an instrument to measure Islamic spirituality, exploratory (using SPSS version 18.0) and confirmatory (using AMOS version 18.0) factor analyses were conducted. The construct validity of Islamic spirituality led to the major finding of the research, thus, Islamic spirituality in the business organizational context is explained by four determinants; Rituals (Ibadat), Forgivingness/Repentance (Al a’fw), Belief (Iman) and Remembrance of Allah (Dhikrullah).